Formação da consciência de classe do docente: um estudo ontológico marxista - Araújo, Júlio César Saunders de (2019)
This research aims to understand the process of formation of the consciousness of the teaching, class. To this end, we chose to study the state education of Ceará, based on aspects that surround the teaching, such as the precarization, the Union and political organization and the fragmentation of the labor activity. It is as theorical-bibliogragic research, planted on the Marxism ontological referential, with emphasis on Marx (1978; 2000; 2002; 2012), Marx e Engels (1982; 1998) and Lukács (2003; 2013). We analyze, in the foreground, the relationship between work, sociability and consciousness so that, from there, we capturethe determinants of the formation of the class consciousness itself and for itself. Finally, we have advanced on aspects that we identified as relevant in relation to the formation of teacher’s class consciousness. In our concluding moment, we assume that the teaching class needs to be aware of its historical role, but this consciousness can be hinted by a series of mechanisms that operate in the logic of reproduction of the capital system, such as alienation, ideology, reformism and abandonment of the centrality of work, replaced by the centrality of politics.